Investigation on the removal of the major cocaine metabolite (benzoylecgonine) in water matrices by UV254/H2O2 process by using a flow microcapillary film array photoreactor as an efficient experimental tool. (1st February 2016) - Russo, Danilo; Spasiano, Danilo; Vaccaro, Marianna; Cochran, Kristin H.; Richardson, Susan D.; Andreozzi, Roberto; Li Puma, Gianluca; Reis, Nuno M.; Marotta, Raffaele
Abstract: A microcapillary film reactor (MCF) was adopted to evaluate and compare the removal efficiency of benzoylecgonine (BE), an emerging micropollutant deriving from illicit drug abuse (cocaine), in different aqueous matrices: milliQ water, synthetic and real wastewater and surface water. The removal processes investigated were the direct photolysis with UV radiation at 254 nm, and the advanced oxidation process (AOP) with the same UV radiation and hydrogen peroxide. As a result of the microfluidics approach developed through an innovative experimental apparatus, full conversion of BE was reached within a few seconds or minutes of residence time in the MCF depending on the process conditions adopted. The radiation dose was estimated to be approximately 5.5 J cm −2 . The innovative MCF reactor was found to be an effective tool for photochemical studies, especially when using highly priced, uncommon, or regulated substances. The removal efficiency was affected by the nature of the aqueous matrix, due to the presence of different xenobiotics and natural compounds that act primarily as HO radical scavengers and secondly as inner UV254 filters. Moreover, nano-liquid chromatography (LC)-high resolution-mass spectrometry analysis was utilized to identify the main reaction transformation products, showing the formation of hydroxylated aromatics during the photochemical treatment. Graphical abstract: Highlights: H2 O2 /UV254 for removing of benzoylecgonine, the major cocaine urinary metabolite An innovative microcapillary photoreactor was adopted for AOPs studies The removal efficiency was affected by the nature of the aqueous matrix Hydroxylated aromatics were detected as phototransformation chemical intermediates